Fabrication and investigation of carbon materials for carbon dioxide capture and hydrogen storage prepared via templating or activation routes - Balahmar, N. (2019)
This thesis details the preparation, fabrication and characterization of nanostructured carbonaceous materials with tuneable porosity for gas storage (CO2 and H2) applications. Two types of carbon-based materials were investigated, namely zeolite templated carbons (ZTCs) and activated carbons (ACs). The ZTCs were prepared using zeolite 13X and zeolite Y as hard templates and furfural alcohol, ethylene, and acetonitrile as carbon precursors. The effects of zeolite compaction before use as hard templates were investigated through the compression of powder forms of zeolites at 370 MPa (equivalent to 5 tonnes) or 740 MPa (equivalent to 10 tonnes) prior to their use as templates. A combination of liquid impregnation (LI) with furfural alcohol and chemical vapour deposition (CVD) with ethylene, or acetonitrile was used to deposit the carbon precursor.